ANALISIS PENGARUH KOMUNITAS ATAU NON KOMUNITAS MUSIK SERTA KESADARAN MEREK TERHADAP MINAT MEMBELI MERCHANDISE LUMAJANG ROCK COMMUNITY - Cahyono, Yofin Agung (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract:The purpose of this research is to test and to analyze the impact of music community or non-community and brand awareness on the purchase intention of merchandise of Lumajang rock community. The population was both members and non-members of music community in Lumajang. The samplesof the research consistof 50 respondents. The analyze method used isdummy regression. The results show that: (1) music community or non-community positively and significantly affects purchase intention ofthe merchandise of Lumajang rock community, (2) top of mind brand positively and significantly affectspurchase intention of the merchandise of Lumajang rock community, (3) brand recall positively and significantly purchase intention of the merchandise of Lumajang rock community, and (4) brand recognitionpositively and significantly affects purchase intention of the merchandise of Lumajang rock community. Keywords:Music Community, Brand Recall, Brand Recognition, Purchase Intention